Regionalna strategia innowacji jako instrument wspierania rozwoju regionalnego na przykładzie Dolnego Śląska - Rogowska, Małgorzata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Progressing integration within the European Union and globalization of world economy are processes that concern more often the issues of innovation and knowledge. The innovation contributes to the creation of competitive superiority of the region, on the national scale. The article describes the idea of regional innovation strategies and present the most important foundation of Lower Silesia's Innovation Strategy. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1143, s. 309-315